USM PROFESSOR RECEIVES HIGHEST AWARD FROM USSH VIETNAM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 9 September 2016 – The foremost expert in the field of Tourism Planning and Development from the Universiti Sains Malaysia (USM) School of Housing, Building and Planning (HBP), Professor Dr. Badaruddin Mohamed recently received the Certificate and Medal of Merit from the University of Social Sciences and Humanities (USSH), Vietnam on his significant contribution in areas of urban development and tourism and also academic involvement in Vietnam.